Unveiling the molecular blueprint of SKP-SCs-mediated tissue engineering-enhanced neuroregeneration - Hui Zhu; Ying Wang; Siyuan Xu; Yunjian Song; Yifan Li; Yiting Wang; Qiuwen Sun; Muyuan Tong; Tianyi Huang; Yulin Pan; Hongkui Wang; Xi Xu; et al. (Journal of Nanobiotechnology)
Abstract Peripheral nerve injury poses a significant challenge to the nervous system’s regenerative capacity. We previously described a novel approach to construct a chitosan/silk fibroin nerve graft with skin-derived precursor-induced Schwann cells (SKP-SCs). This graft has been shown to promote sciatic nerve regeneration and functional restoration to a level comparable to that achieved by autologous nerve grafts, as evidenced by behavioral, histological, and electrophysiological assessments. However, the underlying molecular mechanisms based on SKP-SCs mediated tissue engineering-aid regeneration remain elusive. In the present work, we systematically identified gene modules associated with the differentiation of SKPs into SCs by employing weighted gene co-expression network analysis (WGCNA). By integrating transcriptomic data from the regenerated nerve segment, we constructed a network that delineated the molecular signatures of TENG aid neuroregeneration. Subsequent quantitative PCR (qPCR) validation was performed to substantiate the WGCNA findings. Our WGCNA approach revealed a robust molecular landscape, highlighting hub genes pivotal for tissue engineering-aid regeneration. Notably, the upregulation of specific genes was observed to coincide with the acquisition of SC characteristics. The qPCR validation confirmed the expression patterns of these genes, underscoring their role in promoting neuroregeneration. The current study harnesses the power of WGCNA to elucidate the molecular blueprint governing tissue engineering-aid regeneration. The identified gene modules and validated targets offer novel insights into the cellular and molecular underpinnings of tissue engineering-augmented neuroregeneration. These findings pave the way for developing targeted therapeutics and advanced tissue engineering grafts to enhance peripheral nerve repair.